Bagaimana pola asuh authoritarian mempengaruhi impostor phenomenon pada mahasiswa baru? How does authoritarian parenting affect Impostor Phenomenon in Freshmen? - Syifa Falah Muftiya; Yudi Tri Harsono; Ika Andrini Farida; Angga Yuni Mantara (LP2M Universitas Sarjanawiyata Tamansiswa, 2024)
Impostor Phenomenon is a syndrome that occurs in many freshmen. This phenomenon is closely related to authoritarian parenting. This study aims to determine the effect of authoritarian parenting on impostor phenomenon in freshmen class of 2022, Faculty of Psychology, State University of Malang. This study uses a quantitative approach with a correlational design. The population of this study were freshmen class of 2022, Faculty of Psychology, State University of Malang. The sample used in this study was 91 participants using the quota sampling technique. Data collection used the Parenting Style and Dimensions Questionnaire (PSDQ) on Adolescent which has been adapted to Indonesian by Fahiroh, Tairas, and Retnowati (2019), and adapted the Clance Impostor Phenomenon Scale based on the concept of Dr Clance and Imes (1978). Regression test results showed that authoritarian parenting significantly predicted impostor phenomenon in freshmen (F=17.077; p < 0.05).